The profile and prognosis of patients hospitalised with heart failure. The value of discharge blood pressure amd cholesterol - Jindrich, Spinar; Ondrej, Ludka; Viktor, Musil; Zbynek, Pozdisek; Tomas, Pavlik; Ladislav, Dusek; Jiri, Vitovec; Lenka, Spinarova; Miroslav, Soucek (International heart journal, 2008)
The aim of the present prospective, single centre observational study was to describe the profile and prognosis of patients hospitalised with chronic heart failure and to determine the value of discharge blood pressure and cholesterol for long-term survival. From among 2,346 hospitalised patients, 320 (13.6%) suffered from chronic heart failure and 28 (8.8%) died during hospitalisation. The in-patient mortality rate was similar to that in patients not suffering from chronic heart failure (P = 0, 3). Of 292 patients who were discharged, 162 (55%) died during the subsequent 5 years. The predetermined parameters of pure prognosis were associated with lower diastolic blood pressure (P = 0.008) and lower cholesterol (P = 0.012). A poor prognosis was associated with lower systolic blood pressure plus lower cholesterol and lower diastolic blood pressure and lower cholesterol. Other independent prognostic parameters were older age (P < 0.001), higher heart rate (P = 0.02), higher creatinine (P < 0.001), higher urea (P < 0.001), higher uric acid (P < 0.001), lower hemoglobin (P = 0.02), lower ejection fraction (P = 0.080), and a history of ischemic heart disease (P < 0.01). Patients suffering from chronic heart failure and discharged home have a worse prognosis if their systolic and/or diastolic blood pressures and/or cholesterol levels are too low. The optimal values seem to be levels that are around the recommended targets, that is a systolic BP of 140 mmHg, diastolic BP of 90 mmHg, and a cholesterol level of 5 mmol/L.
Keywords: senioři; propuštění pacienta; Stroke Volume; krevní tlak; Prognosis; Chronic Disease; kreatinin; chronická nemoc; mužské pohlaví; Myocardial Ischemia; Prospective Studies; Hemoglobins; Cholesterol; Heart Rate; kyselina močová; tepový objem; věkové faktory; srdeční frekvence; ženské pohlaví; prognóza; Blood Pressure; Humans; prospektivní studie; Uric Acid; srdeční selhání; hemoglobiny; Patient Discharge; močovina; Age Factors; ischemická choroba srdeční; Creatinine; Urea; Female; Aged; Heart Failure; lidé; Male; cholesterol